The possibility of designing, providing and monitoring training services in accordance with ISO 29993:2017: A case study in the Training and Development Center of the Ministry of Construction, Housing and Public Municipalities in Iraq. (Entrepreneurship Journal for Finance and Business, 2024)
This research aims to test the possibility of designing, providing and monitoring the training service in accordance with the requirements of clauses (8, 10, 13) of ISO 29993:2017 in order to know the size of the gap between the requirements of these clauses of the standard and the actual reality in the training and development center of the Ministry of Construction, Housing and Public Municipalities. Which was chosen as a research sample. The research adopts a case study approach using the Check List as a data collection tool. Statistical methods were used to obtain the research results, represented by (the arithmetic mean and percentage to determine non-conformity and the actual size of the gap). The check list included Three axes, which are as follows (designing the training service, providing the training service, monitoring and evaluating the training service), as they are considered the main stages of the training process. The research reached a set of conclusions, the most important of which is that there is a gap between the actual reality of the researched center and the requirements of clauses (8, 10, 13) of the specification, as the total gap reached (34%) and is due to several long-established reasons that were diagnosed, while the percentage of conformity reached (66%). This is due to the center’s interest in the requirements of providing the training service.The research recommended the necessity of applying the requirements of learning service providers outside formal education in accordance with ISO 29993:2017 to ensure the provision of high-quality training services and giving importance to the subject of documentation by directing departments to document all the operations they carry out in accordance with procedures, work instructions, or records to prove application.